PERAN KUALITAS CORPORATE GOVERNANCE TERHADAP MODEL HUBUNGAN STRUKTUR KEPEMILIKAN, KARAKTERISTIK PERUSAHAAN DENGAN KINERJA PERUSAHAAN - - Triyono; Fatchan Achyani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The paper aims to examine the role of the quality of corporate governance on relationshipownership structure, firm characteristic to performance and risk.  This research used companieswhich are listed on Indonesia Stock Exchange and included Indonesian Most Trusted Companiesin 2008 - 2012 as the samples. The sampling procedure used purposive sampling. The methodanalysis used multiple regressions.The results showed that the institutional ownership positivelyaffect  on the firm performance and negatively effects on risk.The company characteristics thatpositively affects on performance is liquidity, profitability, firm size, and the solvency negativelyaffect on performance. When associated with business risk, profitability and sales growthpositively effect on the risk and size of the company negatively affects on risk. The industry type  negatively affects on performance and positively effects on risk. The quality corporate positivelyeffects on performance, and negatively effects on risk but not significant. These findings suggestthat the quality of corporate governance is an incremental information and complementaryfunction relating to the performance and risk.The debate on the relation between companycharacteristic and a firm’s performance or risk  needs to take directly into account the role ofmoderation and/or mediation of the corporate governance. This paper promotes, as an aim forfuture research, a verification of the validity of this model.       Keywords : quality of corporate governance, ownership structure, firm characteristic,                                         performance, and risk